The cause of advective slowdown of tracer pebbles in rivers: Implementation of Exner‐Based Master Equation for coevolving streamwise and vertical dispersion. Issue 3 (17th March 2016) - Pelosi, A.; Schumer, R.; Parker, G.; Ferguson, R. I.
Abstract: Tracer pebbles are often used to study bed load transport processes in gravel bed rivers. Models have been proposed for their downstream dispersion, and also for vertical dispersion, but not for the combined effects of downstream and vertical movement. Here we use the Exner‐Based Master Equation to characterize the transient coevolution of streamwise and vertical advection‐diffusion of tracer pebbles under equilibrium transport conditions (no net aggradation or degradation). The coevolution of streamwise and vertical dispersion gives rise to behavior that can differ markedly from that associated with purely streamwise processes with no vertical exchange. One example is streamwise advective slowdown. Particles that are advected downward into zones where the probability of reentrainment becomes asymptotically small are essentially trapped and can no longer participate in streamwise advection. As a result, the mean streamwise velocity of the tracer plume declines in time. Qualitative and quantitative comparisons with two field experiments show encouraging agreement despite the simplified boundary conditions in the model. Key Points: The PDF for bed elevation and the PDF for jump elevation show thin tails The EBME is able to capture the streamwise advective slowdown of tracer pebbles Streamwise diffusion shows a superdiffusive behavior due to vertical mixing